1996
DOI: 10.1021/ja953025k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Relative Diatropicity of a Remarkably Aromatic Thia[13]annulene

Abstract: 2,4-Bis(bromomethyl)-3-methylthiophene was synthesised as an intermediate to prepare the strained thiophenobenzophanediene 11, which readily thermally valence isomerizes to the novel thia[13]annulene 10. This thia-annulene is notably diatropic and shows about 40% of the ring current of the parent bridged [14]annulene 9, which is substantially more than an analogous oxaannulene, 18, and substantially less than the azaannulene 19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Both methods will not work for 6 , since there are no vicinal protons and the substituent effect of the dimethylamino group on a most distant proton of 12 cannot be estimated reliably in this case owing to inductive and resonance effects. Although the 13 C NMR spectroscopy signals for the internal methyl groups are known to be less reliable than the proton signals for measuring aromaticity, in some cases they give similar results and here they corroborate our findings. For parent DHP 7 , δ (C17,C18)=14.33 ppm is observed, the reduced reference 2 gives a signal at 23.6 ppm, which would result in RRC( 6 )≈73 % and RCR( 6 )≈27 % (following the same analysis as for the internal methyl proton signals).…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…Both methods will not work for 6 , since there are no vicinal protons and the substituent effect of the dimethylamino group on a most distant proton of 12 cannot be estimated reliably in this case owing to inductive and resonance effects. Although the 13 C NMR spectroscopy signals for the internal methyl groups are known to be less reliable than the proton signals for measuring aromaticity, in some cases they give similar results and here they corroborate our findings. For parent DHP 7 , δ (C17,C18)=14.33 ppm is observed, the reduced reference 2 gives a signal at 23.6 ppm, which would result in RRC( 6 )≈73 % and RCR( 6 )≈27 % (following the same analysis as for the internal methyl proton signals).…”
Section: Figurementioning
confidence: 83%
“…Since 2 has roughly the same geometry as 1 and almost no anisotropy effects are apparent, this system displays one of the very few candidates where a good reference compound is available, hence aromaticity can be evaluated by assuming that aromaticity (or rather resonance energy) is proportional to the ring current (or rather chemical shift) . Comparing the shielding of the internal methyl groups of 1 and an analogue, such as the thia derivative 3 ( δ (Me int )=−1.16 ppm; −1.32 ppm) or the aza derivative 4 ( δ (Me int )=−3.75 ppm; −3.80 ppm), to the same reference compound 2 reveals their aromaticity to be 42 and 95 % of that of DHP 1 , respectively ( 3 : 2.21/5.22=0.42 and 4 : 4.75/5.22=0.91) . Mitchell expanded the scope of DHP as an aromaticity probe by taking advantage of the bond‐localizing effect of aromatic systems fused to the DHP core.…”
Section: Figurementioning
confidence: 99%
“…When we attempted this, we found that the diazonium salt could be formed by slow addition of aqueous sodium nitrite to a vigorously stirred solution of aminothiophene 6 in hydrochloric acid, at Ϫ10 ЊC (it was important that the temperature did not rise above Ϫ5 ЊC as this caused the solution to turn deep purple and become very viscous, presumably due to polymerisation and diazo-coupling reactions). A variety of reducing agents were tried, including hypophosphorous acid, 10 thiophenol, 11 ethanol, 12 and sodium azide. 13 Deaminations using alkyl nitrites in either DMF or acetonitrile 14 (where the solvent acts as the hydrogen donor) were also tried.…”
Section: Resultsmentioning
confidence: 99%
“…Other variations on the reaction conditions are also reported. [9][10][11][12][13] When 2-alkylthiophenes are used as the starting compounds, bromination occurs at the 5-position first (as in 12,14) and then at the 3-position (as in10) (Scheme 4). 5,8,14 D'Aleo et al proposed an alternate method to obtain bromo-substituted alkylthiophenes using ammonium bromide in the presence of hydrogen peroxide in aqueous acetic acid to selectively access the monobromo 7 or the dibromo 8 derivative (Scheme 5).…”
Section: General Preparation Of Halo-substituted Alkylthiophenesmentioning
confidence: 99%
“…Bromo-substituted alkylthiophene derivatives (15,17) were prepared in high yields by electrophilic substitution using bromine (Br 2 ) in solvents such as CHCl 3 or AcOH (Scheme 6). 10,16 The preparation of iodo-substituted alkylthiophenes has also been reported, although the reaction conditions differ from those for the preparation of chloro-or bromo-substituted alkylthiophenes (Scheme 7). Wudl et.…”
mentioning
confidence: 99%